The Relationship Between Postpartum Depression and Breastfeeding - Laili, Uliyatul; Amalia, Rizki (Jurnal Midpro, 2020)
One of the effects of postpartum depression is a decrease in the ability of mothers to care for themselves and their babies, including in the effort to provide breastfeeding. Based on this background, the researcher wanted to research the relationship between postpartum depression and breastfeeding.The research method used was cross sectional research with a total sample of 67 postpartum mothers in the first month. The independent variable in this study was postpartum depression while the dependent variable was breastfeeding. Data were collected using the Edinburgh Postnatal Depression Scale (EPDS) to measure depression during the puerperium.The results showed that 22 respondents who did not experience depression gave breast milk to their babies. Based on data analysis with statistical tests, it was found that p <0.016.There is a relationship between the incidence of postpartum depression and breastfeeding. It is advisable to carry out psychological health monitoring in postpartum mothers to increase the achievement of breastfeeding.